Factors influencing home buyers' purchase decisions in Klang Valley, Malaysia / JieSheng Mang, Rozlin Zainal and Indera Syahrul Mat Radzuan - Mang, JieSheng; Zainal, Rozlin; Mat Radzuan, Indera Syahrul (Universiti Teknologi MARA, Perak, 2020)
Focusing on Klang Valley, this research studies the outcome of house purchase factors in Malaysia. This research identifies the house purchase factors that affect home buyers' purchase decisions. The researcher collected data using SurveyMonkey by using a questionnaire to elicit the opinions of Klang Valley residents on housing purchase factors and purchase decision. The factors were evaluated and studied to identify their influence on home buyers' purchase decision. Findings show that home buyers' purchase decision are influenced by house structure, space, finance, location, and neighbourhood factors. The findings have laid a foundation for the housing industry to improve.